Symmetries and Invariant Solutions for the Thermal Expulsion Equation - Jassim, Maha Falih (Sulaimani Journal for Pure and Applied Sciences, 2007)
In this paper we study the classical Lie symmetries method for a two'dimensional pa*ial differential equation (pOd) wUcn is catted the Thermal Eipulsion EqYdr.oll1l. rve obtained reductions to an ordinary differential equation of a second order (ODE) called priniipal (ODE)'.Then we analyzed some problems of the Thermal Expulsion Equation wtren it is invariant to ihe stretching group to derive an approximate solution of the Expulsion dquation corresponding to impulsive boundary conditions, when these conditions are clamped and a slowly varying happens in them with respect to time again.
Keywords: Lie symmetries; classical symmetries; similarity solutions; and invariant solutions